Anisotropic structure of nanofiber hydrogel accelerates diabetic wound healing via triadic synergy of immune-angiogenic-neurogenic microenvironments - Kunkoo Kim; Jia Yang; Chengli Li; Chun-Yi Yang; Peilun Hu; Yaosai Liu; Yin-yuan Huang; Xiaohan Sun; Ming Chi; Chenyu Huang; Xiaodan Sun; Lingyun Zhao; et al. (Bioactive Materials)
Wound healing in chronic diabetic patients remains challenging due to the multiple types of cellular dysfunction and the impairment of multidimensional microenvironments. The physical signals of structural anisotropy offer significant potential for orchestrating multicellular regulation through physical contact and cellular mechanosensing pathways, irrespective of cell type. In this study, we developed a highly oriented anisotropic nanofiber hydrogel designed to provide directional guidance for cellular extension and cytoskeletal organization, thereby achieving pronounced multicellular modulation, including shape-induced polarization of macrophages, morphogenetic maturation of Schwann cells, oriented extracellular matrix (ECM) deposition by fibroblasts, and enhanced vascularization by endothelial cells. Additionally, we incorporated a VEGF-mimicking peptide to further reinforce angiogenesis, a pivotal phase that interlocks with immune regulation, neurogenesis, and tissue regeneration, ultimately contributing to optimized inter-microenvironmental crosstalk. In vivo studies validated that the anisotropic bioactive nanofiber hydrogel effectively accelerated diabetic wound healing by harnessing the triadic synergy of the immune-angiogenic-neurogenic microenvironments. Our findings highlight the promising potential of combining physical and bioactive signals for the modulation of various cell types and the refinement of the multidimensional microenvironment, offering a novel strategy for diabetic wound healing.